Hubungan Pengetahuan Anak dan Orang Tua tentang Menjaga Kesehatan Gigi dan Mulut dengan Indeks Karies Gigi pada Anak Usia 6-7 Tahun di SD Negeri 1 Gunaksa - Made Dwi Erawati; I Gusti Ayu Fienna Novianthi Sidiartha; Putu Lestari Sudirman (School of Dentistry Faculty of Medicine Udayana University, 2021)
Introduction: Caries is one of the dental health problems that usually happened to children in elementary school. Caries is manifested as a tooth decay process caused by demineralization of enamel, dentin, and cementum. The def-t index is used an instrument to measure the primary teeth decay process by caries. Knowledge is important that has a contribution to how people do their daily life and behavior. It also gives contribution to maintain of their oral and dental health. The children of elementary school usually have lack awareness about oral and dental health so that their parents have a fundamental contribution to guide their children. The purpose of this study is to know correlation between knowledge of children and their parents about maintenance of oral and dental health with caries index of children between 6-7 years old at the elementary school of one Gunaksa. Method: This study is used an observational-analytical design with cross sectional design. This study had been held at elementary school of number one Gunaksa. This study had been done on 45 children between 6-7 years old with their parents too. Children and their parents had given a questionnaire that continuied with the examination of their children def-t index. Result: The Average of the def-t index = 9,91. According to statistical result based on sig (2 tailed) that had explained the correlation between children knowledge and def-t index = 0,857 (not significant result) meanwhile the correlation between their parent knowledge and def-t index also based on sig 2-tailed formula = 0,047 (significant result). Conclusion: The conclusion of this study is children’s knowledge is not correlated to caries index otherwise, parents knowledge is correlated to caries index of children between 6-7 years old in elementary school of the one Gunaksa. Latar Belakang: Karies gigi merupakan salah satu masalah kesehatan gigi dan mulut yang sering terjadi pada anak usia sekolah. Karies adalah kerusakan gigi akibat adanya suatu demineralisasi pada gigi yaitu hilangnya mineral pada enamel, dentin dan sementum pada gigi. Indeks def-t digunakan untuk mengukur kerusakan karena karies pada gigi sulung. Pengetahuan memiliki peranan penting untuk terbentuknya sikap dan perilaku seseorang termasuk dalam menjaga kesehatan gigi dan mulut. Kesadaran anak sekolah dasar masih kurang dalam menjaga kesehatan gigi dan mulut dan peran dari orang tua masih diperlukan oleh anak. Tujuan dari penelitian ini adalah mengetahui hubungan pengetahuan anak dan orang tua tentang menjaga kesehatan gigi dan mulut dengan indeks karies gigi pada anak usia 6-7 tahun di SD Negeri 1 Gunaksa. Metode: Penelitian menggunakan desain observational analitic dengan pendekatan cross sectional. Lokasi penelitian bertempat di SD Negeri 1 Gunaksa. Penelitian dilakukan pada 45 orang anak usia 6-7 tahun beserta orang tua. Anak dan orang tua diberikan kuisioner dan dilanjutkan dengan pemeriksaan indeks def-t anak. Hasil: Rata-rata indeks def-t = 9,91. Berdasarkan penelitian hubungan pengetahuan anak dengan indeks def-t didapatkan hasil nilai sig (2- tailed) = 0,857 (tidak signifikan) sedangkan pengetahuan orang tua dengan indeks def-t nilai sig (2- tailed) = 0,047 (signifikan). Kesimpulan: Kesimpulan dari penelitian ini bahwa pengetahuan anak tidak berhubungan dengan indeks karies gigi akan tetapi pengetahuan orang tua berhubungan dengan indeks karies gigi pada anak usia 6-7 tahun di SD Negeri 1 Gunaksa.